Materials science and engineering of carbon : characterization - Inagaki, Michio; Kang, Feiyu (Butterworth-Heinemann is an imprint of Elsevier, 2016)
Materials Science and Engineering of Carbon: Characterization discusses 12 characterization techniques, focusing on their application to carbon materials, including X-ray diffraction, X-ray small-angle scattering, transmission electron microscopy, Raman spectroscopy, scanning electron microscopy, image analysis, X-ray photoelectron spectroscopy, magnetoresistance, electrochemical performance, pore structure analysis, thermal analyses, and quantification of functional groups. Each contributor in the book has worked on carbon materials for many years, and their background and experience will provide guidance on the development and research of carbon materials and their further applications.
Keywords: Nanostructured materials.; Carbon.; elektronické knihy; electronic books